Wildlife health in human-modified landscapes: epidemiology of tick-borne pathogens affecting black-backed jackals and caracals - Viljoen, Storme (Department of Biological Sciences, 2017)
Despite the importance of disease as a wildlife management challenge, baseline research on the epidemiology of pathogens occurring in wildlife populations within both rural and urban landscapes has received little attention to date. The aim of this study was to improve our understanding of wildlife health in human-modified landscapes in South Africa, by providing comparisons of body condition, host-attached tick diversity and tick-borne pathogen (TBP) epidemiology of two common mesocarnivore species, the black-backed jackal (Canis mesomelas) and caracal (Caracal caracal). Jackals (n=46) and caracals (n=27) were sampled from small livestock farmlands in the Central Karoo region, in addition to caracals from farmlands in Namaqualand (n=14), and the urban matrix of the Cape Peninsula (n=16). Body condition was evaluated using both ratio (Body Mass Index) and residual (Ordinary Least Squares) methods, and morphometry was compared with historical datasets for each species. There was no apparent effect of sex, age class or location on body condition of jackals or caracals. Host-attached tick diversity was highest in urban caracals compared with the two other caracal populations, possibly indicating that they are exposed to a greater diversity of potential tick vectors. Molecular methods (mPCR/RLB; conventional PCR screening and phylogenetic analysis) used to screen for selected pathogens of veterinary and/or zoonotic concern, including Ehrlichia, Anaplasma, Babesia and Theileria species, revealed that Central Karoo jackals exhibited a lower prevalence of TBPs, compared with sympatric caracals. Hepatozoon canis, a ubiquitous pathogen of domestic and wild canids globally, was observed in 46.5% of jackals. Theileria ovis, a piroplasm of small livestock, was found in 4.7% of jackals. Jackals and caracals appear to be distinct in their TBP epidemiological roles, despite sharing similar tick communities. Pathogens found in caracals include Hepatozoon felis, Babesia felis, Babesia leo and a potentially undescribed Babesia species, genetically similar to B. venatorum, an emerging zoonosis. An Anaplasma species previously described in South African domestic dogs was also found in the urban caracals. All caracals were infected with at least one TBP. Together, these findings suggest that land use does not significantly influence the body condition of these adaptable predators, but that there is a health cost associated with living in the urban space. Cape Peninsula caracals show substantially higher rates of TBP co-infection (81% versus 14.8% and 0% in farmlands) and greater pathogen diversity compared to farmland caracals. The findings of this study include numerous examples of previously undescribed genetic diversity of tick-borne pathogens infecting South African mesocarnivores living in transformed landscapes. This work adds to our understanding of wildlife health within the 'One Health' framework and represents the first detailed examination of TBPs in jackals on farmlands and is also the first work that focuses specifically on TPBs in caracals anywhere in the world.